Size Shortening of Body Parts of Fetus Mice (Mus musculus L.) After Giving Bitter Melon Fruit Extract (Momordica charantia L.) - Andriani, Silvia; Nurcahyani, Nuning; Busman, Hendri; Sutyarso; Kurniawaty, Evi; Sahroni, Mizan; Puspa, Egita Windrianatama (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
Bitter melon (Momordica charantia L.) is a plant that has traditional medicinal properties. In bitter melon fruit, there are several toxic compounds, namely momordicoside K and L, which are thought to have cytotoxic properties. This study aims to determine the teratogenic effect of bitter melon fruit extract given to pregnant females on the length of the fetus' cranium and sternum. Bitter melon fruit extraction was carried out using the maceration method using 95% ethanol. By using a completely randomized design 20 male mice and 20 female mice were divided into 4 groups. Each group consisting of 5 pregnant female mice was given bitter melon extract orally starting from day 6 to day 17 of pregnancy once a day in the morning with a treatment dose of aquabidest as a control [A], [B] 22.5 mg/30 gr BW, [C] 30 mg/30 gr BW, and [D] 37.5 mg/30 gr BW. Next, the female mice were dissected, the fetus was removed and the length of the cranium and the length of the sternum were measured. The results showed that in general, the administration of bitter melon fruit extract caused a decrease in the average length of the cranium and sternum. The results of the further analysis with the Least Significant Difference (LSD) at the 5% level showed that administering doses of [B], [C], and [D] had a significant effect on reducing the length of the cranium and sternum. The most effective dose to reduce the length of the cranium and sternum of fetal mice is 37.5 mg/30 g BW